PENGARUH GAYA HIDUP DAN DIFERENSIASI TERHADAP KEPUTUSAN PEMBELIAN HP IPHONE PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UM BENGKULU - Rajib Pagulintra; Sri Ekowati (Yayasan Insani Mandiri Santani, 2025)
This study aims to determine the effect of lifestyle and differentiation on the decision to purchase an iPhone for students of the Faculty of Economics and Business, UM Bengkulu, both partially and simultaneously. The object of this study was students of the Faculty of Economics and Business, UM Bengkulu Class of 2021-2022 with a sample of 130 people. This study used data collection methods by means of observation and distributing questionnaires. The data analysis technique used in this study used instrument testing, respondent response analysis, classical assumption testing, multiple linear regression analysis, coefficient of determination (R2) and hypothesis testing. The results of this study indicate that lifestyle has a positive and significant effect on purchasing decisions in students of the Faculty of Economics and Business, UM Bengkulu. The differentiation variable shows a positive and significant effect on students of the Faculty of Economics and Business, UM Bengkulu. From the results of the study, it can be concluded that lifestyle and differentiation have a partial and simultaneous effect on purchasing decisions in students of the Faculty of Economics and Business, UM Bengkulu. Keywords : Lifestyle, Differentiation and Purchasing Decisions